Buah Buton in Traditional House Interior: Representation of Women's Role and Influence - Maamor, Fakhrur Razi; Kahn, Sabzali Musa; Taif, Basitah (UI Scholars Hub, 2024)
Buah buton is a three-dimensional wooden carving as an interior object in the traditional house of Negeri Sembilan. The purpose of this article is to establish a link between the buah buton in Luak Tanah Mengandung, Negeri Sembilan and the position of women who connect the legacy and leadership in the Adat Perpatih, a customary community law, and how such a relationship manifests itself within the traditional house's interior. The function of buah buton was revealed through fieldwork and interviews with community leaders, which were then combined into a narrative that represented the function of buah buton. The findings revealed the presence of buah buton design hung in certain positions in certain houses, mainly in women-dominated areas. The design and position of the buah buton represent the concept of feminism, which refers to the nature and character of women applied to the visual shape and position of the subject. This aspect is associated with the house’s interior, such as the mother's house and tiang seri, which represents the unique characteristics of women and their influence in the Adat Perpatih. Through exploration of the psychological and cultural aspects of the mother's house within Adat Perpatih, this article intends to gain a deeper understanding of the societal framework. This inquiry will shed light on the distinct ways in which these environments shape and reflect women’s pivotal roles and influences in their society.